Find derivative of y with respect to x.
Sin(xy) = Sinx Siny
The Attempt at a Solution
Use chain rule (product rule for inner function) to differentiate the left. Use product rule to differentiate the right and I get the following:
cos(xy)(y+xy') = (cosx siny) + (cosy' sinx)
distribute the cos(xy) on the left to get:
ycos(xy) + xy'cos(xy) = (cosx siny) + (cosy' sinx)
Rearrange to get y' on one side, everything else on the other.
ycos(xy) - cosx siny = -xy'cos(xy) + cosy' sinx
Now what? I don't understand how I'd solve for y' from here. Inverse cosine?